SYNTACTIC SHIFTS IN ENGLISH-INDONESIAN TRANSLATION (A Case Study of the Fifth Semester Students of the English Department of State University of Semarang) - Noviyanti, Eman Risqi; Nugraha, Laurentius Elyas (ELT Forum: Journal of English Language Teaching, 2016)
This final project is about syntactic shift used in English-Indonesian translation by the fifth semester students of the English Department of State University of Semarang in the academic year of 2013/2014. The objectives of the study are to describe what types of syntactic shifts are commonly used and less used by the fifth semester students, and to explain how the fifth semester students do syntactic shift in English-Indonesian translation. The study uses descriptive qualitative approach and it belongs to a case study. The subject of the study is the fifth semester students of the English Department of State University of Semarang in the academic year of 2013/2014. The source of data is the studentsâ translation tests which have been done in the fifth semester entitled Advantages of Translation. It was a task given by Dr. Rudi Hartono, S.S. M.Pd. as the lecturer in English-Indonesian Translation class in fifth semester. From five sub-categories of syntactic shift, there are three sub-categories of them which were used by the fifth semester students. Translation by using word-into-phrase shift reaches a total of 86.4%. About 10.2% is the translation by using phrase-into-clause shift. The other 3.4% is the translation by using clause-into-sentence shift. Both phrase-into-sentence and sentence-into-paragraph shifts are not found in the studentsâ assignments of English-Indonesian translation.